Validating a questionnaire to assess knowledge and stigmatization of ASD in the Peruvian population: a real need: Validar un cuestionario para evaluar el Conocimiento y la Estigmatización del TEA en la población peruana: una necesidad real - Delgado-Zegarra, Ana (2024)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by difficulties in social interaction, communication, and restricted and repetitive patterns of behavior. Over the past few decades, there has been an increase in awareness and early detection of ASD, significantly improving opportunities for intervention and support. However, individuals with ASD often face stigmatization and discrimination due to a lack of understanding about their condition, which can negatively affect their emotional and social well-being. Therefore, it is crucial to promote greater education and awareness about ASD to reduce stigma and foster a more inclusive society.